Rancang Bangun Sistem Absensi Karyawan Lapangan Pada PT. Albany Corona Lestari Cabang Lebak Berbasis Web - Usman, Andi Usri; Juniansha, Dedi; Fauzi, Diki Gufron (Teknik Informatika Fakultas Ilmu Komputer, 2022)
Attendance is an important thing for an agency or company. Attendance says it is important because it can affect the salary or wages of an employee and attendance can also see the performance of an employee who is often present or absent. Therefore, the attendance process requires accuracy in its implementation so as not to hinder company performance. The purpose of this research is to design an employee attendance information system which is expected to help the performance of the company, especially in the Human Resources sector, to be faster and more practical. The research method used in this employee attendance information system is descriptive research method, while for the development of the system using a waterfall which includes requirements, system analysis, system design, system creation, system implementation, and system maintenance which is expected to assist in developing systems with work experience this clerk. This application development program uses a web-based application. In this system the data processing becomes more effective and efficient. The search for data is guaranteed to be easier.